In vivo and in vitro anti-inflammatory effects of Sophora flavescens residues. (5th October 2018) - Ma, Hongyan; Huang, Qi; Qu, Wenshan; Li, Linyuan; Wang, Min; Li, Shao; Chu, Fujiang
Abstract: Ethnopharmacological relevance: The dried roots of Sophora flavescens Ait. (Leguminosae) is traditionally used as antipyretic medicine to reduce inflammation. It is well known that alkaloids and flavonoids are the main constituents of S. flavescens . However, the clinical researches and applications of S. flavescens is mainly based on its water-extracted alkaloids, its flavonoids may still remain in residues and have been underused. With development and manufacturing of S. flavescens in recent years, more herb residues are being produced. Since they are typically treated as waste and dumped openly in landfill sites, which can cause pollution, there is a great need to explore these wastes as recyclable resources and increase their added value. To date, whether other bioactive components would be found in the residues of S. flavescens is still unknown. If the extraction method of these active ingredients was established, the residues of S. flavescens could be turned from the harm to a benefit and make great sense of the comprehensive utilization of S. flavescens resources. This study aimed to establish an extraction method of the residues of S. flavescens and investigate the anti-inflammatory effect of it both in vivo and in vitro . Materials and methods: Dried S. flavescens were decocted with distilled water firstly, then the residues were powdered and extracted with ethyl acetate by using ultrasonic wave. HPLC was utilized to analyze the chemical constituents of the water extracts of S. flavescens (WSF) and the ethyl acetate extracts of residues of S. flavescens (RSF). In vivo, the anti-inflammatory effect of WSF and RSF were evaluated using the xylene-induced auricle edema, acetic acid-induced peritoneal permeability and carrageenan-induced hind paw edema methods. In vitro, the inhibitory activities of WSF and RSF on NO, TNF-α, IL-6 and MCP-1 production of LPS-treated RAW264.7 cells were measured. Results: The major ingredients of RSF were flavonoids, while WSF almost had no flavonoids. In vivo, WSF and RSF (200 mg/kg) could significantly inhibit the edema in the xylene-induced mice auricle edema and carrageenan-induced hind paw edema as well as the peritoneal permeability increased by acetic acid. They can also lower production levels of PGE2 in inflamed paw tissues. In vitro experimental results showed that RSF (25-100 μg/mL) could significantly inhibit the release of pro-inflammatory cytokines NO, TNF-α, IL-6 and MCP-1 on LPS-induced RAW264.7 cells. The in vitro suppress effect of WSF had no dose-response relationship. Conclusions: The residues of S. flavescens had obvious flavonoids with anti-inflammatory activity. This study provided evidence for the reuse of residues from S. flavescens in the food additive, medicine and cosmetic industries. Graphical abstract: fx1